2019
DOI: 10.1186/s12913-019-4253-4
|View full text |Cite
|
Sign up to set email alerts
|

Mindset modification of community pharmacists in a collaborative relationship between a major hospital and neighboring community pharmacies: a qualitative study

Abstract: Background Patient information sharing between hospitals and community pharmacies is generally insufficient. Since August 2013, the pharmacy department of Kyoto University Hospital has initiated and mediated a collaborative relationship between physicians and neighboring community pharmacies (e.g., sharing outpatient blood test results, holding regular meetings among professionals, delivery of tracing reports from community pharmacists to physicians about outpatients). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Thus, transmitting an exclusive body of knowledge is as important as teaching skills, which allow pharmacists to interact with patients and other professionals. 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, transmitting an exclusive body of knowledge is as important as teaching skills, which allow pharmacists to interact with patients and other professionals. 53 , 54 …”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the proportion of separate dispensing and prescribing functions is over 70% [ 18 ], and patients go to the community pharmacy with the prescription issued by the doctor. Information sharing between hospital and pharmacy about outpatients is rarely done, with pharmacists providing medication guidance based solely on information elicited from patients [ 19 ]. Lack of effective communication between medical professionals and patients in acute care hospitals may contribute to difficulties in transitioning to palliative care [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists, for example, pursue more active roles that challenge their current skill mix within the healthcare system [22]. Studies have indicated that community pharmacists' motivation for CPS provision increased when they worked in multidisciplinary teams and received positive appraisal by other healthcare professionals (e.g., in smoking cessation programs) [77,78]. Results from these studies suggest the importance of positive feedback.…”
Section: Motivationmentioning
confidence: 99%